Preventive Effect of Curcumin Against Chemotherapy-Induced Side-Effects - Liu, Zhijun; Huang, Pengyun; Law, Siukan; Tian, Haiyan; Leung, Wingnang; Xu, Chuanshan (Frontiers in Pharmacology, 2018)
Cancer is still a severe threat to the health of people worldwide. Chemotherapy is one of main therapeutic approaches to combat cancer. However, chemotherapy only has a limited success with severe side effects, especially causing damage to normal tissues such as bone marrow, gastrointestine, heart, liver, renal, neuron, and auditory tissues, etc. The side-effects limit clinical outcome of chemotherapy and lower patients’ quality of life, and even make many patients discontinue the chemotherapy. Thus, there is a need to explore effective adjuvant strategies to prevent and reduce the chemotherapy-induced side effects. Naturally occurring products provide a rich source for exploring effective adjuvant agents to prevent and reduce the side effects in anticancer chemotherapy. Curcumin is an active compound from natural plant Curcuma longa, which is widely used as a coloring and flavoring agent in food industry and a herbal medicine in Asian countries for thousands of years to treat vomiting, headache, diarrhea, etc. Modern pharmacological studies have revealed that curcumin has strong antioxidative, anti-microbial, anti-inflammatory and anticancer activities. Growing evidence shows that curcumin is able to prevent carcinogenesis, sensitize cancer cells to chemotherapy, and protect normal cells from chemotherapy-induced damages. In the present article, we review the preventive effect of curcumin against chemotherapy-induced myelosuppression, gastrointestinal toxicity, cardiotoxicity, hepatotoxicity, nephrotoxicity, neurotoxicity, ototoxicity and genotoxicity, and discuss its action mechanisms.